1998
DOI: 10.22358/jafs/69975/1998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbadox or formic acid and diet type on ileal digestion of amino acids by pigs

Abstract: Endogenous flows and true ileal digestibilities of amino acids were determined with the homoarginine method in growing pigs fed barley-soyabean meal or by-product-soyabean meal diets plus 50 mg/kg carbadox, or 8 g/kg formic acid (85% v/w) or without either of these additives. Seven barrows (one reserve) equipped with T-cannulae according to the steered-ileo-caecal-valve method were fed these diets in a 6 x 4 cyclic change-over design from 39 to 83 kg live weight. Both carbadox and formic acid improved the appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
(9 reference statements)
1
5
0
1
Order By: Relevance
“…1 pH unit ( Table 1), a finding consistent with previous studies (Partanen et al, 1998;Silander-Rasi, 1998). However, this reduction in dietary pH did not impact on gastric or intestinal pH.…”
Section: Methodssupporting
confidence: 92%
“…1 pH unit ( Table 1), a finding consistent with previous studies (Partanen et al, 1998;Silander-Rasi, 1998). However, this reduction in dietary pH did not impact on gastric or intestinal pH.…”
Section: Methodssupporting
confidence: 92%
“…Paulicks et al (2000) found that ADG increased and feed conversion improved in response to K-diformate on lower-energy diets compared with diets approximately 5% greater in energy density. Improved apparent ileal digestibility of Lys, due to decreased endogenous Lys flow, was observed in growing pigs on by-product-based diets (219 g of NDF/kg of DM) but not on barley-based diets (188 g of NDF/kg of DM; Partanen et al, 1998). The differing fiber content of the diets could be a factor; however, the difference was small.…”
Section: Discussionmentioning
confidence: 92%
“…Nursery pigs fed diets containing different grains had improved feed conversion in response to Kdiformate on barley and wheat-based diets but not on corn-based diets (Paulicks et al, 2000). Many previous experiments used diets that were barley-, oat-, or wheat-based (Baustad, 1993;Siljander-Rasi et al, 1998;Partanen et al, 1998Partanen et al, , 2002andCanibe et al, 2001, 2005). Diets in the current experiment were corn-based.…”
Section: Discussionmentioning
confidence: 99%
“…It confirmed the lowered estimation of TRP requirement of broilers published by NRC (1994). Partanen et al (1998) found in pigs an improvement of apparent ileal CP and several amino acids digestibility in the presence of organic acids, they attributed it to the reduced endogenous nitrogen and amino acid losses. In our study the presence of acidifier in diets did not affect significantly either ileal digestibility of amino acids, or apparent nitrogen retention and performance of chickens in comparison with groups fed diets without acidifier.…”
Section: Discussionmentioning
confidence: 98%